2022
DOI: 10.1007/s11064-022-03720-y
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Long Non-coding RNAs in Spinal Cord Injury

Abstract: Spinal cord injury (SCI) can result in a partial or complete loss of motor and sensory function below the injured segment, which has a significant impact on patients' quality of life and places a significant social burden on them. Long non-coding RNA (LncRNA) is a 200–1000 bp non-coding RNA that has been shown to have a key regulatory role in the progression of a variety of neurological illnesses. Many studies have demonstrated that differentially expressed LncRNAs following spinal cord injury can participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…[8,9] Researchers have revealed the critical roles of lncRNAs in SCI. [10,11] X-inactive-specific transcript (XIST) refers to a class of noncoding RNAs implicated in the differentiation and proliferation of cells. [12] Previous studies have revealed that XIST promotes neurological repair post-SCI by binding to miR-32-5p to modulate Notch-1.…”
mentioning
confidence: 99%
“…[8,9] Researchers have revealed the critical roles of lncRNAs in SCI. [10,11] X-inactive-specific transcript (XIST) refers to a class of noncoding RNAs implicated in the differentiation and proliferation of cells. [12] Previous studies have revealed that XIST promotes neurological repair post-SCI by binding to miR-32-5p to modulate Notch-1.…”
mentioning
confidence: 99%